Which club does your alliance belong to? An empirical classification of strategic alliances in post-transition Hungary - Zoltán Buzády (Journal for East European Management Studies, 2005)
The article focuses on possible typologies of strategic alliance. The first section gives a brief overview of the major groupings of alliances followed by the detailed description of strategic alliance history in Hungary. Former alliance theories were not able to describe sufficiently the characteristics of Hungarian strategic alliances because those theories origin in the business environment of western economies. The author presents a new classification of strategic alliances of post-transitional Hungary based on empirical researches. Three new groups arise, namely cautious partner, members only club and waiting for the white knight. – – Der folgende Beitrag hat die Typologisierung von strategischen Allianzen zum Thema. Im ersten Teil werden die wichtigsten Modelle zur Einordnung von Allianzen vorgestellt, anschließend wird das Umfeld sowie die Entwicklung von Unternehmenskooperationen in Ungarn erörtert. Da jedoch alle bisherigen Klassifizierungsmodelle in erster Linie dem westlichen Wirtschaftsumfeld entspringen, können diese die Besonderheiten ungarischer Unternehmenspartnerschaften nicht ausreichend beschreiben. Der Autor präsentiert eine neue, auf umfassenden empirischen Studien fundierte Einteilung der strategischen Allianzen im Post-transitionsland Ungarn, so entstehen die drei neuen Gruppen:Sicher ist Sicher, Der Members-Only Klub sowie Die Traumtänzer.
Keywords: 650; Strategic alliances; strategic management; organisational change; post-transition economies; empirical research